The Belt and Road Initiative’s impact on Textile and Clothing Supply Chains in Asia: Views from Hong Kong Industrial Stakeholders - Man Hin Eve Chan; Chi Kuen Danny Ho; Tsz Leung Yip; Jenny Cheung; Angappa Gunasekaran (International Journal of Applied Business and International Management, 2019)
The global supply chains in the Textile and Clothing (T&C) industry have been shaping by various forces, among them economic development policy is one of the strongest. Amid the rollout of the Chinese’s new national development strategy—Belt and Road Initiative (BRI), major T&C companies see both opportunities and challenges in optimizing and restructuring the networks of their production facilities. One notable and growing trend associated with the BRI is the relocation of T&C manufacturing from China to ASEAN countries and establishment of new factories along the Belt and Road (B&R). Much has been examined about the BRI at the national level, yet little is known about how companies in the T&C industry have responded to this grand economic development plan. This study aims to explore from industrial stakeholders’ perspectives, the factors that drive and hinder synergistic, mutually beneficial development of T&C production and trade among the B&R countries. To achieve this aim, it addresses the following questions: what are the challenges and opportunities faced by T&C companies establishing or relocating production to B&R countries, and what tangible actions have been taken by them? In-depth interviews were carried out with ten industry professionals from Hong Kong-based companies and government institutions involved with T&C trade in the Asian B&R countries, such as Bangladesh, Cambodia, Indonesia and Myanmar. The findings of this study highlight the importance of pursuing sustainable development. On one hand, there is full of potential for T&C companies to achieve cost-effective production along the B&R countries through harnessing economic policy and transport infrastructure that facilitate trade. On the other hand, T&C companies see challenges in managing culturally diversity in the workplace as opportunities for pursuing corporate development in a socially responsible manner. In sum, this study reveals mutual supportiveness of economic and social aspects of T&C production and trade.